2014
DOI: 10.1080/09712119.2014.980419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of egg weight on egg quality traits in partridge (Alectoris Chukar)

Abstract: In this study, the aim was to determine the internal and external quality traits of partridge (Alectoris chukar) eggs as well as the Pearson correlation coefficients among these traits. For use in this research, a total of 200 partridge eggs were collected over three sequential days. The partridges were housed at the Research Unit of Animal Science, Faculty of Agriculture, University of Akdeniz. The eggs were categorized according to weight and classified as ≤19.0 g, 19.1-20.0 g, 20.1-21.0 g and ≥21.1 g. Avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
13
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 26 publications
(26 reference statements)
8
13
2
1
Order By: Relevance
“…The relevance of these traits may be ascribed as suggested by Ukwu et al [ 63 ], who reported significant differences in yolk weight and albumen height among light (less than 49.99 g), medium (50–55 g), and heavy eggs (more than 55 g) of Isa Brown egg layer chickens in Nigeria. This has also been reported by Alkan et al [ 64 ], who addressed a parallel increase in yolk diameter as egg weight increases in partridge eggs. However, no differences between Utrerana and Leghorn breeds were detected in previous studies [ 14 ].…”
Section: Discussionsupporting
confidence: 80%
“…The relevance of these traits may be ascribed as suggested by Ukwu et al [ 63 ], who reported significant differences in yolk weight and albumen height among light (less than 49.99 g), medium (50–55 g), and heavy eggs (more than 55 g) of Isa Brown egg layer chickens in Nigeria. This has also been reported by Alkan et al [ 64 ], who addressed a parallel increase in yolk diameter as egg weight increases in partridge eggs. However, no differences between Utrerana and Leghorn breeds were detected in previous studies [ 14 ].…”
Section: Discussionsupporting
confidence: 80%
“…Selvan et al(2014) reported a significant correlation between albumen and yolk percentage with egg weight, but with a negative relationship for yolk and positive for albumen. Alkan et al (2015) reported a positive correlation between egg weight and shell thickness which is similar to what was found in the current study (Table 2). In disagreement with the present results, Benoît et al (2014) found a nonsignificant correlation between shell thickness and egg weight of red-necked ostrich.…”
Section: Results and Discussion:-supporting
confidence: 91%
“…However, basic information required to develop this industry is unavailable. While the chicken egg has been extensively studied for its internal and external qualities, as well as, for its composition, such information is not so well documented in other poultry species such as ostrich (Alkan et al, 2015). Therefore, the aim of the study was to evaluate the ostrich egg quality characteristics.…”
mentioning
confidence: 99%
“…Les corrélations obtenues présentent certainement un réel intérêt puisqu'elles doivent nous permettre de prédire la qualité interne de l'oeuf à partir de certains paramètres externes, facilement mesurables sans devoir casser les oeufs (non-invasifs) d'une part, et d'améliorer la qualité de l'oeuf par la sélection génétique, d'autre part. Des constatations tout à fait comparables ont été rapportées par d'autres auteurs (Alkan et al, 2015 ;Oczelik, 2002;Kul et Seker, 2004). Selon Alkan et al (2008), la largeur de l'oeuf constitue le critère le plus précis pour prédire la hauteur du vitellus.…”
Section: Corrélations Phénotypiques Entre Les Paramètres De L'oeufunclassified